Peningkatan Literasi Keuangan untuk Mengurangi Perilaku Konsumtif Siswa SMA di Era Dompet Digital - Nurmiati; Murbayani; Ismail; Bastian Lubis (LOSARI DIGITAL, 2026)
This Community Service Activity aims to improve the financial literacy of high school students so they can manage their finances wisely in the era of digital wallets. In addition, this activity aims to raise students' awareness of the risks of consumptive behavior due to the ease of digital transactions, as well as to form disciplined, critical, and responsible financial attitudes in everyday life. The implementation method is designed with an experience-based learning approach or